An exploratory study on the critical features of construction project planning software - Okudan, Ozan; Cevikbas, Murat; Isikin, Zeynep (YILDIZ TECHNICAL UNIV, 2023)
Although planning is one of the most crucial processes of the project management process group, the significance of planning software features has not been elaborated comprehensively. The absence of this theoretical foundation causes confusion among construction practitioners when it comes to select software that meets their expectations. Therefore, in this study, it is aimed to figure out the main features of planning software along with their significance. Firstly, an in-depth literature review was conducted to detect the features of the planning software. Later, a focus group discussion (FGD) conducted with 10 experts who worked in the planning domain was organized to validate or omit the findings obtained from the literature. Next, a questionnaire survey was conducted with the same experts to score the planning features. After the Fuzzy Analytical Hierarchy Process (AHP) analysis, the ranks of the planning features were obtained. The results revealed that Cost Management, Resource Management, and Project Performance Measurement were the top three feature categories. Under each category, the following features were deemed as the most important features: Resources Allocation, Defining of Different Unit Price Types, Earned Value Analysis, Activity Code, Assigning Calendars to the Lags and Resources and Allowing Different Calendars in a Project. It is believed that the outcomes of this study provide a deep insight into the critical features that should be integrated into planning software. In other words, this study conducts a need analysis for the planning software. In this way, planning software developers focus on the most important features.
Keywords: Construction Projects; Fuzzy Analytical Hierarchy Process; Multi-Criteria Decision-Making Project Planning; Planning Software; PERFORMANCE EVALUATION; FOCUS GROUP; FUZZY-AHP; FRAMEWORK; INDUSTRY; DELAY; Engineering